Problems Of Children’s Social Emotional Development - Arif Rahman (Universitas muhammadiyah Banjarmasin, 2021)
The achievement of motor, cognitive, language, and social-emotional abilities in each early childhood varies. There are some social-emotional developmental problems in early childhood that are easily found in children in our daily lives. These problems include cowardice, squeezing, inferiority, shyness, disobedience. The method used in literature studies is activities or activities related to scientific works based on real theory by connecting fields or empirical reality. I nteraksi early childhood with others when everyday, early childhood has different behaviors and feelings and it will affect the behavior that will appear when the child interacts with others.